Microphone frequency response calibrator using low cost embedded device - Neo, Wei Sheng (2017)
According to the International standard for sound level meters (SLM) IEC 61672-1, two performance categories are defined, class 1 and 2. In general, specifications for class 1 and 2 SLM have the same design goals and differ mainly in the tolerance limits and the range of operational temperatures. However, the cost of standard SLM is very high and it's not a viable solution for a project that required large scale of SLM for noise detection. Hence, this project aims to address such problem by introducing MEMS Microphone Frequency Response Calibrator using low cost embedded system that is capable of calibrating the off the shelf MEMS microphone into class 2 SLM.